The complex realities of educational stakeholder collaboration in mathematics education at an international K12 American institution: a qualitative case study - Altidor, Rebecca (My University, 2025)
Math education continues to face challenges with curriculum alignment, equality of instruction, and equitable student support. This study is grounded in constructionism (Crotty, 1998) which views knowledge as socially fabricated and influenced by hierarchical power dynamics, and Apple (2019) and Ayers (2009) contend that institutions reinforce ideologies, control what knowledge is, and who is allowed access to it. This study examines the impact that collaboration between educational stakeholders has on enacting math curriculum to meet students learning needs at an international K12 American institution. I conducted a qualitative case study utilizing a survey and semi-structured interviews with math teachers, instructional coaches, curriculum coaches, principals, and directors. Findings highlight how instrumental institutional support is in shaping instructional practices, challenges faced in implementing instructional strategies, and how inconsistencies in administrative support impact curriculum implementation. Conclusions underscore the need for stronger institutional coherence through math curriculum alignment and collaborative teaching opportunities in the classroom. Future research should examine how senior leadership stakeholders at international K12 American institutions without a background in math develop instructional polices to evaluate curriculum effectiveness.
Keywords: Educational stakeholders; Math curriculum; International K12 American institution; Instructional practices; Collaboration; Student learning